2019
DOI: 10.3390/cryst9080412
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Generation of Millimeter-Sized Glycine Crystals in Non-Seeded Millifluidic Slug Flow

Abstract: Millimeter-sized α-glycine crystals were generated from continuous non-seeded cooling crystallization in slug flow. The crystallization process is composed of three steps in sequence: slug formation, crash-cooling nucleation, and growth. Stable uniform slugs of three different aspect ratios (slug length/tubing inner diameter) were formed, by adjusting the flow rates of both the solution and air streams. Besides supersaturation, the slug aspect ratio can also affect primary nucleation outcome. Stable slug flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 80 publications
4
33
0
Order By: Relevance
“…This can be achieved by simply extending the processing time; therefore, more slugs are generated. However, as already mentioned, this type of scale-up is only suitable for a several times higher productivity. If the ordinary scale-up of a slug flow crystallizer is performed (larger dimensions of a system), the process dynamics can be severely affected. , A larger diameter can also cause the difficulty of splitting two phases into slugs . The scale-up of slug flow crystallizers can also have a negative effect on mixing in slugs, which has already been shown at the microchannel level …”
Section: From Batch To Continuous Processes: the Influence Of Operati...mentioning
confidence: 99%
See 1 more Smart Citation
“…This can be achieved by simply extending the processing time; therefore, more slugs are generated. However, as already mentioned, this type of scale-up is only suitable for a several times higher productivity. If the ordinary scale-up of a slug flow crystallizer is performed (larger dimensions of a system), the process dynamics can be severely affected. , A larger diameter can also cause the difficulty of splitting two phases into slugs . The scale-up of slug flow crystallizers can also have a negative effect on mixing in slugs, which has already been shown at the microchannel level …”
Section: From Batch To Continuous Processes: the Influence Of Operati...mentioning
confidence: 99%
“…If the ordinary scale-up of a slug flow crystallizer is performed (larger dimensions of a system), the process dynamics can be severely affected. 63,64 A larger diameter can also cause the difficulty of splitting two phases into slugs. 41 The scale-up of slug flow crystallizers can also have a negative effect on mixing in slugs, which has already been shown at the microchannel level.…”
Section: From Batch To Continuous Processes: the Influence Of Operati...mentioning
confidence: 99%
“…Mou et al. studied the production of glycine crystals by using the slug‐flow tubular crystallization method without adding seed crystals 18. The results showed that the aspect ratio of the slug also affected the results of primary nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the slugflow crystallization method can usually be applied to obtain better crystal product quality in continuous-flow tubular crystallization [17]. Mou et al studied the production of glycine crystals by using the slug-flow tubular crystallization method without adding seed crystals [18]. The results showed that the aspect ratio of the slug also affected the results of primary Mingpu Yuan 1 Jingkang Wang 1,2 Xin Huang 1,2,3, * Ting Wang 1,2,3 Na Wang 1,2,3 Lina Zhou 1,2 Hongxun Hao [19].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue collects six studies on different aspects of anti-solvent crystallization development, with a particular focus on pharmaceutical crystallization. In the first contribution, continuous crystallization of glycine was developed in slug flow crystallizer [1]. A crash cooling stage was introduced in the entry section to induce nucleation.…”
mentioning
confidence: 99%